A blueprint for food safety in China. Issue 1 (1st February 2016) - Connolly, Aidan J; Luo, Leona Shaojing; Woolsey, Michael; Lyons, Mark; Phillips-Connolly, Kate
Abstract : Purpose: – The purpose of this paper is to offer a blueprint, or outline considerations for the continuing evolution of the Chinese food safety system. Design/methodology/approach: – The paper begins with the review of the current food safety system in China and the demonstration of the successes in national food safety programmes. It goes on to identify the specific problems through food sully China, and further to analyse the potential for implementing the key learnings from other national food safety programmes in the Chinese context. Findings: – The paper suggests a five-point Blueprint for food safety in China and other countries, allowing for the development of a robust food safety system, by combining the elements with best practice from system created by food safety practitioners internationally. Research limitations/implications: – It should be noted that even since the authors began developing this model China has already adopted a number of the recommendations covered by this Blueprint and is actively considering others. Originality/value: – This paper fulfills an identified information/resources need and offers a blueprint, or outline of considerations for the continuing evolution of the Chinese food safety system.